Library Information System Design at Library And The Archives Agency Of Tangerang City - Haris, H.; Permatasari, Silvia; Saputro, Rizki Bayu (Pandawan Sejahtera Indonesia, 2021)
The library is one of the containers used by the community to look for a variety of literature reviews in the form of books, catalogs and journals. A computerized library information system is needed to improve the quality of library services. This study aims to create a computerized system that can be used by librarians and library visitors easily. In this study, researchers used the PIECES method (Performance, Information, Economy, Control, Efficiency, Service). For designing the model using UML (Unified Modeling Language). The design concept uses MVC (Model View Controller). The design framework used is Bootstrap and CI, while the programming language uses PHP HTML CSS and Javascript. With this library information system, it is expected to facilitate the performance of officers in serving library visitors.